Maternal Experience of Intimate Partner Violence Is Associated with Suboptimal Breastfeeding in Malawi, Tanzania, and Zambia: Insights from DHS Analyses (P10-059-19). (13th June 2019) - Walters, Christine; Rakotomanana, Hasina; Komakech, Joel; Stoecker, Barbara
Abstract: Objectives: Maternal experience of intimate partner violence (IPV) remains an overlooked variable in the context of breastfeeding in East Africa. Therefore, this study investigated the association between maternal experience of different forms of intimate partner violence (IPV) and frequency of IPV and suboptimal breastfeeding practices in Malawi, Tanzania, and Zambia. Methods: Data were obtained from the most recent Demographic and Health Surveys for Malawi ( n  = 1878), Tanzania ( n  = 3184), and Zambia ( n  = 3879) and included mother-infant dyads. Outcomes were early initiation of breastfeeding, exclusive breastfeeding, and continued breastfeeding. IPV was maternal reported experience of physical, sexual, or emotional violence or controlling behaviors and frequency of IPV. Significant bivariate results ( P  < 0.05) were included in the adjusted models in multivariate logistic regression. Results: Most (80.4%) Malawian mothers initiated early breastfeeding, compared to mothers in Tanzania (53.4%) and Zambia (67.7%). Just over half (55.0%) of Tanzanian infants were exclusively breastfed while 60.1% and 70.6% of Malawian and Zambia infants were. Continued breastfeeding at 1 year was high in all countries; Malawi (91.0%), Tanzania (92.4%), Zambia (95.0%). In Zambia, 78.8% of mothers reported experiencing any form of IPV compared to 76.6% and 73.4% of Tanzanian and Malawian mothers who reported experiencing IPV. In all three countries, mothers who experienced emotional IPV were more likely not to initiate breastfeeding in the first hour after birth (Malawi [AOR = 1.37(1.05–1.79)]; Tanzania [AOR = 1.43(1.22–1.68)]; Zambia [AOR = 1.28(1.06–1.54)]). In Malawi and Zambia, women who frequently experienced any form of IPV were more likely not to have exclusively breastfed (Malawi [AOR = 1.88(1.17–3.04)]; Zambia [AOR = 1.96(1.35–2.85)]). Tanzanian mothers who experienced emotional IPV were nearly two times more likely not to continue breastfeeding until the child's first birthday [AOR = 1.94(1.03–3.66)]. Conclusions: In all three countries, maternal experience of IPV was associated with suboptimal breastfeeding practices. The potential effects of maternal experience of IPV on breastfeeding should be considered when planning interventions and designing policies to improve breastfeeding in Malawi, Tanzania, and Zambia. Funding Sources: None.